A Theory of Hypocrisy - Alice Hallman; Daniel Spiro (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper explains the occurrence of hypocrisy – when the by-society most despised types pretend to be the most revered types. Real-world phenomena include pedophile priests, sex-offender feminists and seemingly very busy dispensable office workers. Building on the signaling framework of Bernheim (1994) – where payoffs consist of an intrinsic cost of falsifying yourself, and a concern for social esteem – we show conditions for emergence of hypocrisy in equilibrium. In such equilibria the most despised types along with the most revered types behave normatively, others do not. Thus, in equilibrium there are “rumors” about those acting the most normatively – society infers that they are either truly normative or despised, but one cannot know who is who. This is to be distinguished from “conformity” – where the most normative and almost-normative types fully follow a social norm. Whether conformity or hypocrisy will arise in equilibrium depends on the cost of falsification, and the number of hypocrites depends on the weight of social esteem. Our theory thus shows how cultural parameters map into equilibrium culture.
Keywords: D70; D91; Z10; 330; social esteem; hypocrisy; conformity; social norm